Finite rank self-adjoint perturbations - Nizhnik, L. P.; Kuzhel, S. A. (Methods of Functional Analysis and Topology, 2006)
Finite rank perturbations of a semi-bounded self-adjoint operator A are studied. Different types of finite rank perturbations (regular, singular, mixed singular) are described from a unique point of view and by the same formula with the help of quasi-boundary value spaces. As an application, a Schrödinger operator with nonlocal point interactions is considered.